Analysis of smoke control models at long tunnel: A case study on the Hsuehshan tunnel - Wei Chiu, Chen-; Sheng Huang, Chi-; Hsun Chen, Chiun- (Scientific Journal of Environmental Sciences, 2017)
This study used the Fire Dynamics Simulator (FDS) to simulate a fire in a 5000 meters long section of the Hsuehshan tunnel (12.9km in total length). Actual distances were considered in jet fan simulations and steady-state velocity profiles were simulated in tunnel portals. A worst-case analysis was performed for the area between two vertical shafts in the tunnel. To prevent the smoke from becoming an obstacle in the Hsuehshan tunnel, fans located 250 meters upwind and 500 meters downwind of the fire source were deactivated. The smoke control system currently used in the Hsuehshan tunnel includes activation of four jet fans upwind of the fire and intermittent operation of jet fans downwind of the fire. This system was examined in this study as benchmark model Eva1 and compared with the alternative evacuation plans Eva2, Eva3 and Eva4. The results indicated that, regardless of fan activation, the downwind area of the fire remained dangerous. With regard to upwind safety, it was calculated that adults with an average walking speed of 1.2m/s and weak evacuees with an average walking speed of 0.64m/s would need 205 and 227 seconds respectively to traverse 30 meters. In Eva1 and Eva2, for 15MW, 30MW and 65MW heat release rates (HRRs), tunnel users situated within 30 meters from the fire source would not be able to escape safely.